Pediatric Orthopedics : Symptoms, Differential Diagnosis, Supplementary Assessment and Treatment - Visser, Jan Douwes (Springer International Publishing : Imprint: Springer, 2017)
This book presents the most common site-specific pediatric orthopedic problems seen in clinical practice. Detailed discussions of disorders of the chest wall, neck, back, pelvic, upper- and lower limb, leg length discrepancy, abnormal gate, congenital deficiencies, bone and joint infections are included in this comprehensive resource. Operative treatments are discussed throughout the book with the key focus on managing the patient and the use of the conservative approach. As such, the main benefit of this book is as a diagnostic tool to assess children with orthopedic disease. Designed to lead the reader from the initial physical examination through to making the most likely diagnosis, there is advice on what additional studies are meaningful, when there is an indication for referral and what advice can be provided for the patient. The value of the book is increased by hundreds of color images, thus making it easily accessible for pediatric orthopedic surgeons, pediatrician s, pediatric physiotherapists, podiatrists, pediatricians, rehabilitation specialists and primary care physicians with an interest in the subject.